Ultrasound of pre and postnatal hydronephrosis - Brito, Brunna Jhessika Sbardella; Brito, Maurício Sbardella; Souza, Alex Moreira (Brazilian Journal of Implantology and Health Sciences, 2024)
Dilation of the pelvis and renal calyx is called hydronephrosis (HN), which occurs in 1 to 5% of all pregnancies. HN is identified by ultrasound (US) which, due to its popularization, has led to an increase in HN diagnoses during prenatal care. US is the exam of choice because it provides diverse information, is widely available, has low cost and is non-invasive.